2017
DOI: 10.1016/j.apsb.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures, absolute configurations and molecular docking studies of naftopidil enantiomers as α 1D -adrenoceptor antagonists

Abstract: Chiral drug naftopidil (NAF), a specific α1D-adrenoceptor (AR) antagonist for the treatment of benign prostatic hyperplasia, was used in racemic form for several decades. Our recent work declared that NAF enantiomers showed the same antagonistic effects on the α1D-AR, but the binding mechanism of these two stereochemical NAF isomers to the α1D receptor remained unclear. Herein, we reported the crystallographic structures of optically pure NAF stereoisomers for the first time and unambiguously determined their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…permeability (Xu et al, 2017;Blume & Schug, 1999;Chavda et al, 2010;Tsume et al, 2014). There are no reports in the literature on either salts or cocrystals of naftopidil; therefore, we aimed to prepare new solid forms of naftopidil as part of a cocrystal screen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…permeability (Xu et al, 2017;Blume & Schug, 1999;Chavda et al, 2010;Tsume et al, 2014). There are no reports in the literature on either salts or cocrystals of naftopidil; therefore, we aimed to prepare new solid forms of naftopidil as part of a cocrystal screen.…”
Section: Resultsmentioning
confidence: 99%
“…Naftopidil(Xu et al, 2017) is a selective 1-adrenergic receptor antagonist alpha-blocker antihypertensive drug. In the Biopharmaceutical Classification System (BCS) it is classified as a class IV drug of poor aqueous solubility and poorresearch papers 818 Rambabu Dandela et al 6-component organic-salt alloy of naftopidil IUCrJ (2018).…”
mentioning
confidence: 99%
“…In order to precise their results, experiments using membrane preparations from CHO cells stably expressing the cloned human α 1 -AR genes showed that naftopidil has 17- and 3-fold higher potency for α 1D -AR than for the α 1B - and α 1A -AR, respectively [ 41 ]. Yuan’s team showed similar results through docking studies and on rat functional assay in vitro and highlighted that naftopidil used as a racemate, as well as its S- and R- enantiomers had similar blocking activity on α 1 -AR subtypes [ 42 , 43 ]. However, a recent work contradicted these previous observations and showed that naftopidil affinity is α 1A > α 1B > α 1D [ 44 ].…”
Section: Alpha 1 -Adrenergic Receptor Antagonismentioning
confidence: 95%
“…Hence, the almost identical molecules of two enantiomers might exhibit various crystallization tendencies. 21 Interestingly, the dynamics of the enantiomeric systems does not strongly differ, and therefore their effect on the crystallization process might be excluded. 22 Consequently, enantiomers and their mixture seem to be interesting candidates to examine the role of thermodynamics on the crystallization process.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the pharmaceuticals’ stability behavior, one should take into account that those materials frequently occur in various enantiomeric forms, which crystallize to the different primitive cells. Hence, the almost identical molecules of two enantiomers might exhibit various crystallization tendencies . Interestingly, the dynamics of the enantiomeric systems does not strongly differ, and therefore their effect on the crystallization process might be excluded .…”
Section: Introductionmentioning
confidence: 99%